Behavioural weight management programmes for adults assessed by trials conducted in everyday contexts: systematic review and meta‐analysis. Issue 11 (11th August 2014) - Hartmann‐Boyce, J.; Johns, D. J.; Jebb, S. A.; Summerbell, C.; Aveyard, P.; Behavioural Weight Management Review Group
Summary This systematic review and meta‐analysis of effectiveness trials comparing multicomponent behavioural weight management programmes with controls in overweight and obese adults set out to determine the effectiveness of these interventions implemented in routine practice. To be included, interventions must have been multicomponent, delivered by the therapists who would deliver the intervention in routine practice and in that same context, and must be widely available or feasible to implement with little additional infrastructure or staffing. Searches of electronic databases were conducted, and augmented by screening reference lists and contacting experts (November 2012). Data were extracted by two reviewers, with mean difference between intervention and control for 12‐month change in weight, blood pressure, lipids and glucose calculated using baseline observation carried forward. Data were also extracted on adverse events, quality of life and mood measures. Although there were many published efficacy trials, only eight effectiveness trials met the inclusion criteria. Pooled results from five study arms providing access to commercial weight management programmes detected significant weight loss at 12 months (mean difference −2.22 kg, 95% confidence interval [CI] −2.90 to −1.54). Results from two arms of a study testing a commercial programme providing meal replacements also detected significant weight loss (mean difference −6.83 kg, 95% CI −8.39 to −5.26). In contrast, pooled results from five interventions delivered by primary care teams showed no evidence of an effect on weight (mean difference −0.45 kg, 95% CI −1.34 to 0.43). One study testing an interactive web‐based intervention detected a significant effect in favour of the intervention at 12 months, but the study was judged to be at high risk of bias and the effect did not persist at 18 months. Few studies reported other outcomes, limiting comparisons between interventions. Few trials have examined the effectiveness of behavioural weight loss programmes delivered in everyday contexts. These trials suggest that commercial interventions delivered in the community are effective for achieving weight loss. There is no evidence that interventions delivered within primary care settings by generalist primary care teams trained in weight management achieve meaningful weight loss.